Democracy in the Digital Age challenges to political life in cyberspace - Wilhelm, Anthony G. (New York : Routledge, 2000)
A fascinating and incisive treatment of a hot topic. This is a philosophical exploration of how emerging information and communication technologies are impacting on political participation in the United States.
Book Cover; Title; Contents; Acknowledgments; INTRODUCTION; CYBERDEMOCRACY'S ~TROUBLED AND FROTHY SURFACE~; SHAPING VIRTUAL CIVIC SPACES; RESOURCE REQUIREMENTS OF DIGITALLY MEDIATED POLITICAL LIFE; IMMUNE TO PROGRESS: RECONCEPTUALIZING AMERICA'S INFORMATION AND TELECOMMUNICATIONS UNDERCLASS; VIRTUAL SOUNDING BOARDS: HOW DELIBERATIVE IS ONLINE POLITICAL ACTIVITY?; DESIGNER DEMOCRACY; CATCHING THE RED QUEEN: PUBLIC-POLICY RENOVATIONS; CONCLUSION: MEDIA CAMPAIGNS AND THE NEW INTERNATIONAL; Logistic Regression Analysis of Home Computer Ownership.
Includes bibliographical references (pages 163-176) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Political participation -- Computer network resources; Internet; World Wide Web; Electronic books